Delineation of MidXq28-duplication syndrome distal to MECP2 and proximal to RAB39B genes - Sinibaldi, Lorenzo; Parisi, Valentina; Lanciotti, Silvia; Fontana, Paolo; Kuechler, Alma; Baujat, Genevieve; Torres, Barbara; Koetting, Judith; Splendiani, Alessandra; Postorivo, Diana; Beygo, Jasmin; Garaci, Francesco G.; et al. (Clinical Genetics, 2019)
Two distinct genomic disorders have been linked to Xq28-gains, namely Xq28-duplications including MECP2 and Int22h1/Int22h2-mediated duplications involving RAB39B. Here, we describe six unrelated patients, five males and one female, with Xq28-gains distal to MECP2 and proximal to the Int22h1/Int22h2 low copy repeats. Comparison with patients carrying overlapping duplications in the literature defined the MidXq28-duplication syndrome featuring intellectual disability, language impairment, structural brain malformations, microcephaly, seizures and minor craniofacial features. The duplications overlapped for 108 kb including FLNA, RPL10 and GDI1 genes, highly expressed in brain and candidates for the neurologic phenotype.
CRIS-Team Scopus Importer:2019-06-28
Keywords: corpus callosum and cerebellar vermis hypoplasia; developmental delay/intellectual disability; microcephaly; Xq28-duplication